Uma proposta de uso de ICMS Ecológico para iniciativas de educação ambiental em Foz do Iguaçu-PR - Brasil, Iêda Beatriz Closa (2021)
The Ecological ICMS (ICMS-E) is a strengthening tool to implement conservation policies that can add results in the field of environmental education. The present work presents a proposal to increase the capture of Ecological ICMS by the municipality of Foz do Iguaçu - PR, guiding its application to support the environmental education initiatives. The research is characterized as a case study, from a qualitative approach, the results of which demonstrated that there is a potential for conservation of 21 area fragments in the rural and urban areas of the municipality in question, which may favor the increase of the collection in ICMS-E around R$ 500 thousand annually. The research collaborated to demonstrate the relevance of the presence of protagonism in the municipal management to implement the requirements of the legislation of the ICMS-E and, in a guiding character, indicated a plan that supports the reversal of this resource to strengthen the application of environmental education projects coordinated by the Coletivo Educador Municipal de Foz do Iguaçu.